VERTICAL DIVERSITY OF EPIPHYTIC DIATOMS ON STEMS OF Rhizophora sp AND FRONDS OF Nypa sp IN KUNDUR WATERS KARIMUN REGENCY, RIAU ISLANDS PROVINCE - Rini, Yulia Sapta; Efriyeldi, Efriyeldi; Siregar, Sofyan Husein (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
This study was conducted in the waters of Kundur Island, Karimun Regency, Riau Islands Province, to assess the type, abundance, and diversity of epiphytic diatoms on Rhizophora sp stems and Nypa sp fronds using a survey method and purposive sampling for station selection. One-way ANOVA, LSD tests, and the Independent Samples T-test were employed for data analysis. The research identified 11 species of epiphytic diatoms: 9 from the Bacillariophyceae class (including Navicula sp, Pleurosigma sp, Pinnularia sp, and Skeletonema costatum); Isthmia sp from the Coscinodiscophycidae class, and Chaetoceros sp from the Bacillariophyceae class. The results indicated a higher abundance of diatoms on Nypa sp fronds (17,822.94 ind/cm²) than on Rhizophora sp stems (13,884.16 ind/cm²). Significant differences in diatom abundance were observed between stations on Rhizophora sp. stems, particularly between stations II and III. In contrast, no significant differences were found between stations I and II or stations I and III. No significant differences in diatom abundance were observed between stations on Nypa sp fronds. The T-test results revealed significant vertical differences in diatom abundance between Rhizophora sp stems and Nypa sp fronds. Overall, the diversity of epiphytic diatoms was categorized as medium on both Rhizophora sp stems and Nypa sp fronds in the waters of Kundur Island, Karimun Regency, Riau Islands Province. This study contributes valuable insights into the ecological dynamics of epiphytic diatoms in mangrove and nipa palm habitats.